Self‐Assembly of a Guanosine Derivative To Form Nanostructures and Transmembrane Channels. Issue 16 (19th February 2018) - Das, Rabindra Nath; Kumar, Y. Pavan; Kumar, S. Arun; Schütte, Ole Mathis; Steinem, Claudia; Dash, Jyotirmayee
Abstract: We herein report the self‐assembly of a lipophilic bromoguanosine derivative (G1 ) in homogeneous solution, in the solid state and in planar bilayer membranes. The self‐assembly ofG1, driven by H‐bonding and π–π stacking interactions can form different nano‐structures depending on incubation time. TheG1 nanostructure is able to bind a bioactive dye like Rose Bengal. In crystal state, it shows ribbon type H‐bonding pattern and exhibits birefringence in polarized light. And further, the self‐assembled nanostructure ofG1 can form discrete transmembrane ion channels in lipid bilayer membranes, enabling passage of potassium ions. Abstract : Nucleoside nanostructure and ion channel : A simple lipophilic nucleoside analogue forms self‐assembled structures in solution, solid state and in lipid bilayer. Interestingly, the self‐assembled structure of this nucleoside exhibits birefringence, incorporates a bioactive dye and forms transmembrane ion channels across a phospholipid bilayer.